Proceeding - Effect Of Ads And Quality Of Products On Decision Of Purchasing Frisian Flag Product In Medan City - Nel Arianty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
Proceeding - Effect Of Ads And Quality Of Products On Decision Of Purchasing Frisian Flag Product In Medan City